Efficacy evaluation of intravenous immunoglobulin in non-severe patients with COVID-19: A retrospective cohort study based on propensity score matching. (April 2021) - Huang, Chenlu; Fei, Ling; Li, Weixia; Xu, Wei; Xie, Xudong; Li, Qiang; Chen, Liang
Highlights: No statistically significant difference was found between the intravenous immunoglobulin (IVIG) group and the control group in the duration of fever, virus clearance time, length of hospital stay, or use of antibiotics. Compared to the IVIG therapy group, no more patients in the control group progressed to severe disease or died. In non-severe patients with COVID-19, no benefit was observed with IVIG therapy beyond standard therapy. Abstract: Objectives: At the present time, there is an absence of any proven effective antiviral therapy for patients with coronavirus disease 2019 (COVID-19). The aim of this study was to assess the efficacy of intravenous immunoglobulin (IVIG) in non-severe patients with COVID-19. Methods: A retrospective study based on propensity score matching (PSM) was designed. Primary outcomes included the severity and mortality rates. Secondary outcomes included the duration of fever, virus clearance time, length of hospital stay, and use of antibiotics. Results: A total of 639 non-severe patients with COVID-19 were enrolled. Forty-five patients received IVIG therapy and 594 received non-IVIG therapy. After PSM (1:2 ratio), the baseline characteristics were well balanced between the IVIG group ( n = 45) and control group ( n = 90). No statistically significant difference was found between the IVIG group and control group in the duration of fever (median 3 vs 3 days, p = 0.667), virus clearance time (median 11 vs 10 days, p = 0.288), length of hospital stay (median 14 vs 13 days, p = 0.469), or use of antibiotics (40% vs 38.9%, p = 0.901). Meanwhile, compared to the IVIG group, no more patients in the control group progressed to severe disease (3.3% vs 6.6%, p = 0.376) or died (0 vs 2.2%, p = 0.156). Conclusions: In non-severe patients with COVID-19, no benefit was observed with IVIG therapy beyond standard therapy.